University partnerships for academic programs and professional development - Blessinger, Patrick; Cozza, Barbara (Bingley, U.K. : Emerald, 2016)
This volume examines the diverse ways in which universities and colleges around the world are partnering and collaborating with other institutions to fulfill their missions and visions. University partnerships not only include collaborations between universities but also include university-school (basic education) collaborative partnerships to improve local school systems. The increasing pressures to remove access and participation barriers, and the increasing pressures to mitigate practices restricting free flow of education across borders have created a growing global space for educational services of all types. As a result, traditional institutional boundaries have expanded to better respond to increasing pressures on them by the growing demand for higher education services. The boundaries between educational institutions and other entities such as government, business, and non-profit organizations have become more fluid and this has resulted in increased involvement by institutions, faculty, and students in activities outside the traditional boundaries of the classroom. This edited volume will specifically explore university partnerships for academic and program development.
Innovative approaches in university partnerships: an introduction to university partnerships for academic and program development / Barbara Cozza, Patrick Blessinger -- Internationalization: a strategic and complex approach / Laura Carfang -- The centrality of the faculty role in transnational partnerships: a research agenda / Rick Arrowood, Leslie Hitch -- Inter-institutional collaboration through non-positional leadership: a STEM higher education initiative / Sherri Cianca -- Interinstitutional collaboration in Dutch professional higher education / Rutger Kappe, Domien Wijsbroek, Marjon Molenkamp, Olof Wiegert, Gerwin Hendriks, Zuke Ingen, Jaap Zandwijk -- The evolution of a foundation program: reflections on the five year partnership between University College London and Nazarbayev University / Dominic Mahon, Rachel Niklas -- Cross-country faculty learning community: An opportunity for collaboration around the Scholarship of Teaching and Learning / Anabella Martinez, Cathy Bishop-Clark, Beth Dietz -- Home and Away: a case study analysis of a learning and teaching programme supporting the development of a 'transformative' partnership with a private HEI in Sri Lanka / Hazel Messenger, Digby Warren, Wendy Bloisi -- By design and by chance: the story of one international partnership / Inese Berzina-Pitcher, Punya Mishra, S. Giridhar -- Community college-university cross-border partnership through faculty exchange / Iddah Otieno, Tom Otieno -- Small is beautiful - how a young university can successfully establish university partnerships - the Case of FH JOANNEUM University of Applied Sciences / Thomas Schmalzer, Doris Kiendl-Wendner -- University partnerships for academic program and professional development: building faculty capacity for 21st century teaching and learning / Alia Sheety, Elizabeth Moy, Judith Parsons, David Dunbar, Kathleen Doutt, Elizabeth Faunce, Leslie Myers -- Creative cross-cultural connections: Facebook as a third space for international collaborations / Natascha Radclyffe-Thomas, Anne Peirson-Smith, Ana Roncha, Adrian Huang -- The Carnegie Project on the education doctorate: a partnership of universities and schools working to improve the education doctorate and K-20 schools / Jill Perry, Debby Zambo.
Includes indexes.
Includes bibliographical references.
Print version record
Keywords: Education -- Higher; Universities; College-school cooperation; Teachers -- Training of